Association of ruptured sinus of Valsalva aneurysm and congenital ventricular septal defect: a case series. Issue 7 (7th July 2021) - Sarhan, Hatem Hemdan Taha; Shawky, Abdel Haleem; Anilkumar, Smitha; Elmaghraby, Ahmed; Sivadasan, Praveen C; Omar, Amr S; Al-Mulla, Abdul Wahid
Abstract: Background: Ruptured sinus of Valsalva aneurysm (RSOVA) is rare, and it is more common in Asians. Typically, the patient presents with acute/subacute shortness of breath (SOB) and chest pain. Echocardiography is the gold standard for diagnosis in most of these cases. Surgery has remained the first line of management. Case summary: We present two cases of RSOVA in which the patients presented to the emergency department with SOB. Their preoperative echocardiography results showed RSOVA into the right ventricle. During surgical repair, ventricular septal defect (VSD) was also found. Discussion: RSOVA is frequently associated with other congenital anomalies, and most often with VSD. In our cases, we believe that VSDs were missed preoperatively because either the large aneurysmal sacs covered the VSD or there was overlap between the two shunts. Additionally, in the first case, right ventricular pressure was high approaching systemic pressure, which probably reduced the shunt across the VSD. Early intervention is recommended to prevent endocarditis or enlargement of the ruptured aneurysm; long-term results were excellent after surgical repair. Most patients undergo surgery between 20 and 40 years of age, and the reported survival rate is 95% at 20 years. If left untreated, patients typically die of heart failure or endocarditis within 1 year after onset of symptoms.